IoT security through web application firewall - Prema Sindhuri, B; Kameswara Rao, M (International Journal of Engineering and Technology, 2018)
The current trend in home electronics needs to be Internet Connectivity. Internet of Things is a collection of many interconnected objects, services and devices that can communicate and share the data to achieve a common goal in different areas and applications using internet. Attacks on IoT devices are physical attacks, side channel attacks, cryptanalysis attacks, software attacks, network attacks. The network attacks does not require physical access to create a major disruption like DDos in the network. The attackers can insert themselves between us and our devices like Man in Middle Attack. A firewall acts as a barrier between a trusted network and an untrusted network. This is a proposed work to focus on the security challenges of IoT using web application firewall.